Tales from the Periphery – How the EU Border facilitates Cohesion in peripheral Regions - Barthel, Martin (International Journal of Contemporary Economics and Administrative Sciences, 2016)
Overcoming the periphery disadvantages is currently the official spatial policy of the European Union. The concepts of a cohesive community and a Europe of the regions are political priorities. However, the success of regional development depends primary on local practices. This is specifically relevant in border regions, which generally had been contested in the past, leaving a landscape of historical scarves, conflicts and fault-lines. In order to understand if border regions use the demarcation as a resource, it is important to understand how local strategies are implemented, discussed and modified in order to achieve a sustainable development. The paper will provide a short overview on indicators for periphery, it will present local strategies toward the border in the Polish border town Przemyśl and discuss if the development of a peripheral region can be positive influenced, when the border is understood as a regional resource. The paper is based on fieldworkers to the region in 2007 and 2014, during which in-depth expert interviews with local stakeholders had been carried out. The results had been further verified with a complimentary analysis of relevant literature, media and local planning documents.